IDENTIFICATION OF B-CELL AND T-CELL SPECIFIC PEPTIDE VACCINE FOR MORGANELLA MORGANII. - A Monicaa; Sathish Sankar, A Monicaa (Chelonian Research Foundation, 2023)
Introduction:The research tackles the pressing requirement for a specific peptide vaccination against Morganella morganii, a bacteria that poses a considerable risk, particularly to individuals with compromised immune systems. Understanding the drawbacks of conventional antibacterial therapies, attention is now directed toward identifying particular B-cell and T-cell epitopes for a novel peptide vaccine approach. Objectives: To discover an optimal length range-spanning B-cell epitope that exhibits homology to M.morganii adherence. Identifying the T-cell epitope with the best potential score for increased vaccine efficacy. to emphasize a comprehensive immune response and bring our approach into line with current trends in epitope prediction. Materials and Methods: To find the best target, protein databases were thoroughly examined. The B-cell epitope TRNMTHYGINDDNRGLTANKTQ was found, and its length and homology were assessed. It was found that the T-cell epitope with the highest score (0.98705) improved the vaccine's strategic aspects. Using cutting edge computational tools, epitope predictions were made in accordance with accepted practices in the field. Results: The B-cell epitope that was chosen demonstrated complete homology to M.morganii and conformed to the optimal length range, making it a promising contender for incorporation into the vaccine. In synergy with current developments in epitope prediction for a stronger immune response, the top-scoring T-cell epitope adds a critical component to the vaccination approach. Conclusion: This work emphasizes how important epitope identification is as a starting point for developing a targeted peptide vaccine to prevent M.morganii. By improving vaccine efficacy, the chosen epitopes offer a tactical advance in the fight against bacterial infections. But further refinement and validation of these results depend on continuous validation, flexibility, and cooperation between computational and experimental approaches. Keywords: M.morganii , peptide vaccine, B-cell epitope, T-cell epitope, epitope prediction, Vaccines, Diseases, Universal Health, immune response.